Grooving The Shoot Free Throw Drill Training and Concentration on Free Throw Shooting Outcome (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This research aims to find out the relation between concentration levels of players on a free throw and how much the contribution of concentration levels on free throw outcome of basketball players in Unit Mulyoharjo Sekitar (UMS) PREDATOR club in Pemalang Regency. This research used the Purposive Sampling technique. Data collection technique used Grid concentration test. This research is non-experimental research through quantitative descriptive approach with correlational design. The subject of the research was 40 players of UMS PREDATOR. The sample was collected using purposive sampling from the population consisted of all students. The research instrument used grid concentration test and foul shot. Based on the result of data It can be seen from the result of Anova Fvalue = 6.837 > Ftable = 2.021, The result of the third hypothesis shows significant result between factor A (training method of shoot free throw drill) and B (concentration) on free throw shooting skill outcome. The result related to the hypothesis test of interaction proved that there was an interaction between the training method of shoot free throw drill and concentration on free throw shooting outcome.